IMPLEMENTASI MANAJEMEN PEMASARAN DALAM MENINGKATKAN MINAT PESERTA DIDIK BARU DI SMP AL HUDA JATIAGUNG LAMPUNG SELATAN - Utami, Dwi Rahayu; Septuri, Septuri; Fadillah , M. Kharis (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of educational marketing management based on the marketing mix (7Ps) in increasing student interest at SMP Al-Huda Jatiagung, South Lampung. This research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the principal, teachers, and the new student admission committee. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of the marketing mix (7Ps), including product, price, place, promotion, people, physical evidence, and process, has been effectively carried out and contributes significantly to increasing student interest. Superior programs based on Islamic values, affordable pricing strategies, strategic location, adaptive promotional efforts, professional human resources, adequate facilities, and efficient service processes are the key factors attracting public interest. The novelty of this study lies in strengthening the analysis of the 7Ps marketing mix implementation in the context of Islamic education at the junior high school level, demonstrating that the integration of religious values with modern marketing strategies can enhance the competitiveness of educational institutions.